Tinjauan Hukum Islam Mengenai Pembagian Zakat Fitrah Untuk Non-Muslim (Studi Kasus di DKM Al-Hidayah Kp.Pasir Kecamatan Samarang Kabupaten Garut) - Sunarsa, Sasa; Anggraeni, Mia (STAI Al Musaddadiyah Garut, 2023)
Zakat fitrah must be issued by every Muslim during Ramadan and paid before Eid prayers. The group of recipients of zakat fitrah accommodated in the DKM of Al-Hidayah Mosque is not specifically mentioned to be distributed to Muslims only but can be given to non-Muslims. The formulation of the problem is: How is the Distribution of Zakat Fitrah for Non-Muslims in DKM Masjid Al-Hidayah? How is Islamic Law Review Regarding the Distribution of Zakat Fitrah to Non-Muslims in DKM Masjid Al-Hidayah? The purpose of this study is to find out how the distribution of zakat fitrah for Non-Muslims in DKM Masjid Al-Hidayah and find out how the Review of Islamic Law regarding the distribution of zakat fitrah for Non-Muslims in DKM Masjid Al-Hidayah. This research uses a type of field research using descriptive methods through a qualitative approach. The data analysis used is through the stages of data reduction, data presentation and conclusions. Based on the results of this study, it was found that the distribution of zakat fitrah carried out at the DKM of Al-Hidayah Mosque included the Non-Muslim group as the Asnaf Muallaf group. And based on Islamic law, zakat fitrah may not be given to non-Muslims other than to the 8 (eight) asnaf that have been explained in Q.S At-Taubah ayat 60. Keywords: Islamic Law, Zakat Fitrah, Non-Muslim